2020
DOI: 10.2174/1875692117666191211154755
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of the Opioid Receptor µ-1 (OPRM1) A118G Polymorphism, an Opioid Drug Therapy Related Gene, in the Indonesian Population

Abstract: Background: The opioid receptor μ-1 (OPRM1) has become one of the most studied genes in pharmacogenetics, as this gene encodes the μ-opioid receptor (MOR), which plays a role in opioid drugs response, as well as in various disorders. One of its variants, A118G, which is found at a high frequency in the Asian population, has been associated with loss of sensitivity to and an increased requirement for analgesics in the treatment of pain, increased pain sensitivity, various types of substance dependencies, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Based on this description, it can be concluded that this research is in line with the research of Puspitasari et al (2020) which also found that the frequency of the G allele in men was higher than in women. Although in this study, there was no significant difference in the frequency distribution of the SNP A118G allele of the OPRM1 gene based on the sex of the subject with a p value > 0.05 (p = 0.08), while Puspitasari et al getting male sex has a higher G allele frequency distribution with a P value <0.05 (p = 0.029).…”
Section: Differences In Genotype Frequency Distribution In Snp A118g Gene Oprm1 With Gendersupporting
confidence: 86%
See 3 more Smart Citations
“…Based on this description, it can be concluded that this research is in line with the research of Puspitasari et al (2020) which also found that the frequency of the G allele in men was higher than in women. Although in this study, there was no significant difference in the frequency distribution of the SNP A118G allele of the OPRM1 gene based on the sex of the subject with a p value > 0.05 (p = 0.08), while Puspitasari et al getting male sex has a higher G allele frequency distribution with a P value <0.05 (p = 0.029).…”
Section: Differences In Genotype Frequency Distribution In Snp A118g Gene Oprm1 With Gendersupporting
confidence: 86%
“…Then genotype heterozygous mutant (AG) in 33.75% and homozygous mutant genotype (GG) in 38.75% of the total 80 subjects. Puspitasari et al (2020) shows that Indonesia, with the majority of subjects being Javanese, tends to have the highest 118G allele frequency (55.6-60.4%) among Asian countries, followed by ethnic Malays (53.1%). This also supports the theory that demographics may be a contributing factor, given that Malaysia may have the closest demographic and ethnic characteristics to Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, an investigation conducted in Indonesia demonstrated an elevated G allele frequency in males (Puspitasari et al, 2020). The polymorphism showed no significant gender differences in populations from China and the United Kingdom (Bunten et al, 2011;Ding et al, 2013).…”
Section: Discussionmentioning
confidence: 79%